2013
DOI: 10.1111/ans.12407
|View full text |Cite
|
Sign up to set email alerts
|

Single‐incision laparoscopic hernioplasty versus multi‐incision laparoscopic hernioplasty: a meta‐analysis

Abstract: Background: Laparoscopic hernioplasty is the gold standard treatment for inguinal hernias. Recently, single-incision laparoscopic hernioplasty (SILH) has been suggested as an alternative technique. It is not evident whether the benefits of this procedure overcome the potential increased risk. Objective: The aim of this study was to compare the outcomes of SILH with conventional multi-incision laparoscopic hernioplasty (MILH) using a meta-analysis of available controlled clinical trials. Methods: Eligible artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…According to Lai et al , the operative time for unilateral repair took significantly longer with LESS TEP than with conventional TEP ( P = 0.01), but bilateral TEP repairs took similar amounts of time. The Luo et al review reported that both unilateral and bilateral LESS TEP repairs required a longer operative time than their conventional counterparts ( P = 0.001 and P = 0.016, respectively), but were associated significantly less postoperative pain with LESS TEP technique (POD) 7 ( P = 0.021) .…”
Section: Current Evidencementioning
confidence: 97%
See 3 more Smart Citations
“…According to Lai et al , the operative time for unilateral repair took significantly longer with LESS TEP than with conventional TEP ( P = 0.01), but bilateral TEP repairs took similar amounts of time. The Luo et al review reported that both unilateral and bilateral LESS TEP repairs required a longer operative time than their conventional counterparts ( P = 0.001 and P = 0.016, respectively), but were associated significantly less postoperative pain with LESS TEP technique (POD) 7 ( P = 0.021) .…”
Section: Current Evidencementioning
confidence: 97%
“…Five meta‐analyses and reviews were found (Table ). Three studies compared the outcomes of various LESS and conventional LIHR , and the other two studies compared LESS and conventional TEP .…”
Section: Current Evidencementioning
confidence: 99%
See 2 more Smart Citations
“…13 Two previous meta-analyses that were conducted to assess SILH concluded that the procedure is feasible and safe in certain patients when compared to CLH. 7,14 However, in these meta-analyses, the number of included studies was rather small (only 3 and 8 publications, respectively). Additionally, these 2 studies included nonrandomized trials and therefore may exaggerate the inherent bias and confounding in design.…”
Section: Introductionmentioning
confidence: 95%